Adhesive tape, article, and method for detaching article

By using a melt softening layer of thermoplastic resin and inorganic hollow filler in the adhesive tape, combined with the energized heating technology, the problems of thermal deterioration and thermal damage during heating and peeling of the adhesive tape in the prior art are solved, and safe and efficient bonding is achieved Belt disassembled.

CN119220189APending Publication Date: 2024-12-31DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410770241.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The conventional method of peeling the adhesive tape by heating may easily lead to thermal deterioration or thermal damage to the adhesive, and it is difficult to peel off when the heating is insufficient, making it difficult to achieve safe and efficient disassembly.

Method used

Adhesive tape composed of an adhesive layer, a heating element and a melt softening layer. The melt softening layer contains a thermoplastic resin and an inorganic hollow filler. The melt softening layer is melted or softened by heating, thereby achieving peeling of the adhesive tape, and the heating element passes through Power on and heat to control the amount and speed of heating.

Benefits of technology

It realizes safe and efficient peeling of the adhesive tape in a short time, prevents thermal damage to the adhered, simplifies the disassembly process, and is suitable for reuse in electronic equipment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220189A_ABST
    Figure CN119220189A_ABST
Patent Text Reader

Abstract

The technical problem to be solved by the present invention is to provide: an adhesive tape which can be peeled off by heating in a short time, can prevent thermal damage to adherends, and can be easily peeled off by heating; an article in which at least two adherends are adhered via the adhesive tape; and a method for detaching the article. As a means for solving the technical problem, the present invention provides an adhesive tape having at least an adhesive layer, a heat-generating body, and a melt-softening layer adjacent to the heat-generating body in this order, the melt-softening layer containing a thermoplastic resin and an inorganic hollow filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive tape ("adhesion" in Japanese means "sticking"), an article, and a method for disassembling the article. Specifically, the present invention relates to an adhesive tape that can be used in various fields such as the manufacture of electronic devices, an article having a structure bonded by the adhesive tape, and a method for disassembling the article. Background Art

[0002] Adhesive tapes are used as a bonding method with excellent workability and high bonding reliability, and are used for fixing parts, temporarily fixing parts, and labeling to display product information in various industrial fields such as OA equipment, IT products, home appliances, and automobiles. In recent years, from the perspective of protecting the global environment, the demand for recycling and reuse of used products has increased in various industrial fields such as home appliances and automobiles. When recycling and reusing various products, it is necessary to peel off the adhesive tapes used for fixing and labeling parts, but since the adhesive tapes are installed in various places in the product, it is expected to reduce the operating cost through a simple removal process.

[0003] In order to separate adherends from each other, for example, a hot melt adhesive composition that dissolves rapidly in a short time by electromagnetic induction heating has been proposed (for example, see Patent Document 1). As a method for separating adherends from each other, a method for dismantling a building has been proposed as follows: a metal base material is heated by an electromagnetic induction heating device, and the adhesive between the base material and the interior material is heated and foamed to be peeled off, and the interior material is peeled off from the metal base material (for example, see Patent Document 2). In addition, a double-sided adhesive tape having a heat conductive layer has been proposed, wherein the double-sided adhesive tape can be easily disassembled by directly heating the heat conductive layer by contacting with a heat generating source (for example, see Patent Document 3). Prior art literature Patent Literature

[0004] Patent Document 1: Japanese Patent Application Publication No. 2002-188068 Patent Document 2: Japanese Patent Application Publication No. 2006-200279 Patent Document 3: Japanese Patent Application Publication No. 2016-108394 Summary of the invention Technical problem to be solved by the invention

[0005] However, in the previous method of peeling and disassembling by heating, since heat is applied from the outside, if the heat required for peeling the adhesive tape is generated from the heating element, there is a situation where the adherend is sometimes thermally degraded or thermally damaged due to the generated heat. On the other hand, if the thermal degradation and thermal damage of the adherend are to be suppressed, the heat generation is sometimes reduced and the adhesive tape is not sufficiently heated, making it difficult to peel. Therefore, in the adhesive tape that fixes adherends such as rigid bodies to each other, it is desirable to have an adhesive tape that can disassemble and reuse the parts that serve as the adherend, and it is more desirable to have an adhesive tape that can be easily disassembled and peeled by heating.

[0006] The object of the present invention is to provide an adhesive tape that can be peeled off by heating in a short time, can prevent thermal damage to an adherend, and can facilitate the peeling operation by heating, an article having a structure bonded by the adhesive tape, and a method for disassembling the article. Technical solutions for solving technical problems

[0007] The present invention relates to the following (1) to (18). (1) An adhesive tape comprising at least an adhesive layer, a heat generating element, and a melt-softening layer adjacent to the heat generating element in this order, wherein the melt-softening layer contains a thermoplastic resin and an inorganic hollow filler. (2) The pressure-sensitive adhesive tape according to (1), wherein the thermoplastic resin constituting the melt-softened layer comprises a block copolymer or a hydrogenated product thereof, the block copolymer comprising a polymer block containing a structural unit derived from an aromatic vinyl compound and a polymer block containing a structural unit derived from a conjugated diene compound. (3) The pressure-sensitive adhesive tape according to (1) or (2), wherein a content of the inorganic hollow filler in the melt-softening layer is in a range of 5% by volume to 80% by volume. (4) The pressure-sensitive adhesive tape according to any one of (1) to (3), wherein the average particle size of the inorganic hollow filler is in the range of 1 μm to 200 μm. (5) The pressure-sensitive adhesive tape according to any one of (1) to (4), wherein the inorganic hollow filler is at least one selected from the group consisting of a glass hollow filler and a silica hollow filler. (6) The pressure-sensitive adhesive tape according to any one of (1) to (5), wherein the melt-softened layer has a thickness in the range of 10 μm to 200 μm. (7) The pressure-sensitive adhesive tape according to any one of (1) to (6), wherein the thermal conductivity of the melt-softened layer is in the range of 0.03 to 0.20 W / m·K. (8) The pressure-sensitive adhesive tape according to any one of (1) to (7), wherein the temperature range in which the loss tangent (tan δ) of the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softened layer reaches 0.8 or more is 80°C or more. (9) An adhesive tape according to any one of (1) to (8), wherein the temperature at which the loss tangent (tanδ) of the adhesive layer reaches 0.8 or more is higher than the temperature at which the loss tangent (tanδ) of the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softening layer reaches 0.8 or more. (10) The pressure-sensitive adhesive tape according to any one of (1) to (9), wherein the heat generating element has a volume resistivity of 30 μΩ·cm or more at 20°C. (11) The pressure-sensitive adhesive tape according to any one of (1) to (10), wherein the heat generating element has a pair of protruding portions protruding from outer circumferences of the pressure-sensitive adhesive layer and the melt-softened layer in a plan view. (12) The pressure-sensitive adhesive tape according to any one of (1) to (11), further comprising a pressure-sensitive adhesive layer on the opposite side of the surface of the melt-softened layer adjacent to the heat generating element. (13) The pressure-sensitive adhesive tape according to any one of (1) to (12), wherein the melt-softened layer can be peeled off by heating. (14) The adhesive tape according to any one of (1) to (13), wherein the heat generating element is a current-carrying element that generates heat when electricity is passed through it, and the adhesive tape is peeled off by the heat generated by the current-carrying element.

[0008] (15) An article comprising at least two adherends and the adhesive tape according to any one of (1) to (14) between the two adherends, wherein the two adherends are bonded to each other via the adhesive tape. (16) The article according to (15), wherein the heat generating element constituting the pressure-sensitive adhesive tape has a pair of extending portions extending from the outer periphery of the adherend in a plan view. (17) The article disassembly method according to (15) or (16), wherein the two adherends are separated by melting and / or softening the melt-softening layer through heating by the heat generating element. (18) A method for disassembling an article according to (17), wherein the heating of the heating element is resistance heating, the heating element is electrically connected to a power source, current is supplied from the power source to the heating element, and the molten-softening layer is melted and / or softened by resistance heating, thereby separating the two adherends. Effects of the Invention

[0009] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape that can be peeled off by heating in a short time, can prevent heat damage to an adherend, and can be easily peeled off by heating. In addition, the present invention can provide an article having at least two adherends bonded via the adhesive tape and a method for disassembling the article, which can suppress thermal degradation of adherends such as electronic components, enable reuse, and facilitate disassembly work. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a schematic cross-sectional view showing an example of the pressure-sensitive adhesive tape of the present invention. Figure 2 This is a schematic cross-sectional view showing another example of the pressure-sensitive adhesive tape of the present invention. Figure 3 This is a schematic plan view showing another example of the pressure-sensitive adhesive tape of the present invention. Figure 4 This is a schematic plan view showing an example of a pattern of the heat generating element in the pressure-sensitive adhesive tape of the present invention. Figure 5 This is a schematic cross-sectional view showing another example of the pressure-sensitive adhesive tape of the present invention. Figure 6 This is a schematic plan view showing an example of the article of the present invention. Figure 7 This is a schematic cross-sectional view showing an example of the article of the present invention. Figure 8 This is a diagram schematically showing a method for disassembling an article of the present invention. Fig. 9 This is a schematic plan view of the pressure-sensitive adhesive tape of Example 1. Fig.10 This is a schematic cross-sectional view of the pressure-sensitive adhesive tape of Example 1. Fig.11 It is a schematic plan view showing an article and an evaluation method according to an example. Fig.12 It is a schematic front view showing an article and an evaluation method according to an embodiment. Fig.13 It is a schematic side view showing an article and an evaluation method according to an embodiment. Description of Reference Numerals a, a1, a2: Adhesive layer b: Heating element c: Melt softening layer e: Extension (heating element) 10, 20, 30: Adhesive tape 50, 50a, 50b: Adhesive 100: Items 60: Alligator clip 70: Probe P: Press position DETAILED DESCRIPTION

[0011] Hereinafter, the embodiments of the present invention will be described in detail. It should be noted that in the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively.

[0012] 1. Adhesive tape The present invention provides an adhesive tape, which comprises at least an adhesive layer, a heat generating element and a melt-softening layer adjacent to the heat generating element in this order, wherein the melt-softening layer contains a thermoplastic resin and an inorganic hollow filler. The adhesive tape of the present invention has the property that the melt-softened layer can be peeled off by heating, and can be used as an easily removable adhesive tape. After being attached to an adherend and fixed between adherends, the fixation between the adherends can be easily separated or disassembled after a certain period of time. Since the adhesive tape of the present invention has the above-mentioned structure, it is not limited by the material of the adherends, and can maintain high adhesion when fixed between adherends, and can be easily separated or disassembled by heating when the adherends are separated or disassembled. It should be noted that "separation or disassembly" is also referred to as "disassembly" below.

[0013] The adhesive tape of the present invention has a heating element. The heating element is heated by directly energizing it or by heating means such as induction heating, infrared rays, microwaves, etc., which are irradiated from the outside with energy, so that the melt-softening layer adjacent to the heating element is melted or softened. In the present invention, in order to suppress the degradation of the adherend caused by external energy irradiation and to be able to disassemble the article while the adhesive tape is built into the article, the heating element is preferably a current-carrying element that generates heat by energizing it, and the adhesive tape of the present invention is preferably peeled off by the heat generated by the current-carrying element. Here, the adhesive tape of the present invention has a heat-insulating effect of suppressing the conduction of heat generated by the heating element to the adherend by making the melt-softening layer contain an inorganic hollow filler, and at the same time has a heat storage effect in the melt-softening layer. Through the above-mentioned effects, the thermoplastic resin constituting the melt-softening layer can be efficiently melted or softened. Therefore, the adhesive tape of the present invention has a heat storage effect of the melt-softened layer, and as it is heated by the heat from the heating element, the adhesive strength decreases, the residual adhesive force after energization relative to the initial adhesive force is small, and the rate of decrease in adhesive force caused by energization is large. Therefore, the article made using the adhesive tape of the present invention is excellent in disassembly. In other words, the adhesive tape of the present invention generates heat inside the tape, so when an article formed by bonding at least two adherends via the adhesive tape of the present invention is removed, thermal damage to the adherends can be reduced and the article can be easily removed.

[0014] In addition, even in an article made of bonded electronic components that is built into a device, cannot contact the adhesive tape, and is completely shielded from the outside, the electronic components can be easily disassembled from each other without preparing a large-scale device. In particular, when the adhesive tape is thermally disassembled using a drive current in the electronic component while being built into the electronic device, thermal degradation of the circuit in the electronic component can be prevented, and thermal peeling can be performed without the need for an external device, making the disassembly operation easy.

[0015] The adhesive tape of the present invention can be "peeled off by heating" in a manner that: heating causes the adhesive tape, especially the melt-softening layer itself, to melt or soften, thereby causing cohesive failure inside the melt-softening layer, thereby causing part or all of the adhesive tape to be peeled off from the adherend; or heating causes the adhesive tape, especially the melt-softening layer itself, to melt or soften, thereby reducing its adhesive force, causing peeling (interfacial failure) between the melt-softening layer and the layer or adherend adjacent to the melt-softening layer, thereby causing part or all of the adhesive tape to be peeled off from the adherend. In addition, when the adhesive tape is peeled off by heating, the entire melt-softening layer may be peeled off from the adherend, or a portion of the melt-softening layer may be peeled off from the adherend. In addition, as described later, the adhesive layer constituting the adhesive tape of the present invention is composed of a component that is less likely to melt or soften due to heating than the component constituting the melt-softening layer. Furthermore, the melt-softening layer can store heat received from the heating element in the layer and keep it warm by containing an inorganic hollow filler. Therefore, the adhesive tape of the present invention can heat the melt-softening layer by heating the heating element to selectively melt or soften it, and then peel it off. Hereinafter, the structure of the adhesive tape of the present invention will be described.

[0016] 〔Fever body〕 The heating element can be selected from known heating elements according to the heating means used. As heating and heating means, for example, resistance heating, electromagnetic induction heating, infrared heating, microwave heating, heat conduction, etc. can be cited. Among them, from the viewpoint that the melting softening layer can be fully softened or melted even with a small amount of energy, for example, the adhesive tape can be thermally disassembled using the driving current in the electronic component when it is built into the electronic device, and from the viewpoint that the heating element does not need to be heated by an external heat source across the adherend and excessive heating of the adherend can be prevented, resistance heating is preferred.

[0017] Here, "resistance heating" refers to a method of electric heating, which is a method of passing current through a conductive body (heating body) with resistance and using its Joule heat to heat the conductive body. If a constant current is passed through the conductive body, the amount of Joule heat generated in a certain period of time is proportional to the square of the current and the resistance of the wire (Joule's law). The conductive body has a resistance value (volume resistivity, etc.) inherent to its material. "Electromagnetic induction heating" refers to a non-contact heating method among electric heating methods, also known as high-frequency induction heating. If a conductive body (heating body) with resistance is placed in a magnetic field generated by passing a high-frequency current (alternating current) through a coiled conductor, the current flows through the conductive body according to the principle of electromagnetic induction, and the conductive body is heated by the Joule heat thereof. "Infrared heating" and "microwave heating" refer to non-contact heating methods that use electromagnetic waves in a specific wavelength range such as infrared rays and microwaves, and utilize heat energy based on radiation. The atoms that make up a substance are combined, and the molecules undergo thermal vibrations (molecular motion, crystal lattice vibrations) corresponding to the temperature of the substance itself. If electromagnetic waves of a wavelength corresponding to the vibration frequency are absorbed, the vibration of the molecules becomes intense and heat is generated. “Heat conduction” is a heating method that utilizes the heat transfer phenomenon that heat is transferred from a high temperature side to a low temperature side inside a solid. It can transfer heat by bringing a heat generating source into direct contact with a material with excellent thermal conductivity.

[0018] When the heating means is resistance heating, the heating element is preferably an electrically conductive element having resistance, and examples thereof include metals, non-metals, and organic-inorganic composite materials. Examples of metals include nickel-chromium alloy (108 μΩ·cm); stainless steels such as SUS410 (62.2 μΩ·cm), SUS304 (72.0 μΩ·cm), and SUS430 (60.0 μΩ·cm); titanium (55.0 μΩ·cm); nickel silver (for example, "nickel silver C7701" manufactured by Takeuchi Metal Foil Powder Co., Ltd. is 34.0 μΩ·cm), and metal fiber sheets (for example, "stainless steel fiber sheets" manufactured by Tomogawa Paper Co., Ltd.). It should be noted that the values ​​in parentheses represent the approximate values ​​of the volume resistivity of each substance at 20°C. Among them, nickel-chromium alloys and stainless steel are preferred from the viewpoints of being less likely to break when formed into a foil, being easy to handle as an adhesive tape, and being able to melt the melt-softened layer in a short time to significantly reduce the adhesive force. Examples of nonmetals include carbon (3352 μΩ·cm as an example) and other carbon nanomaterials such as graphite, graphene, graphene oxide, carbon nanotubes, graphene platelets, and carbon nanofibers. Among them, carbon nanomaterials such as carbon nanotubes are preferred from the viewpoints that they are easy to process into a film, are not likely to impair the physical properties such as the followability required for the tape, are easy to exhibit conductivity even in a small amount, and can melt the melt-softened layer by resistance heating in a short time. Examples of the organic-inorganic composite material include a metal vapor-deposited film obtained by vapor-depositing a metal such as aluminum or chromium on a polyester film, a woven or nonwoven fabric subjected to conductive plating, and a conductive coating film.

[0019] When the heating means is resistance heating, the volume resistivity of the heating element at 20°C is preferably 30 μΩ·cm or more, more preferably 50 μΩ·cm or more, further preferably 70 μΩ·cm or more, and particularly preferably 100 μΩ·cm or more. From the viewpoint of not excessively increasing the voltage required when energizing the heating element, the volume resistivity of the heating element at 20°C is preferably 100,000 μΩ·cm or less, more preferably 20,000 μΩ·cm or less, further preferably 10,000 μΩ·cm or less, and particularly preferably 5,000 μΩ·cm or less. Specifically, the volume resistivity of the heating element can be in the range of 30 μΩ·cm to 100,000 μΩ·cm, in the range of 50 μΩ·cm to 20,000 μΩ·cm, in the range of 70 μΩ·cm to 10,000 μΩ·cm, and in the range of 100 μΩ·cm to 5,000 μΩ·cm.

[0020] If the volume resistivity of the heating element is 30 μΩ·cm or more, when the article is disassembled, when the heating element is connected to the wiring circuit in the electronic device and the driving current of the electronic device is energized to the heating element, only the adhesive tape can be heated, and high-temperature degradation of the wiring circuit can be prevented. In addition, if a heating element with a volume resistivity in the above range is used, the melt-softening layer can be melted or softened in a short time, and the disassembly time can be shortened. Furthermore, when the driving current in the electronic component is used, it is possible to prevent the electronic circuit and the connection portion from being excessively heated due to the conduction of electricity to the heating element, thereby preventing the electronic component from being thermally deteriorated.

[0021] The volume resistivity of the heating element can be measured at 20° C. using a low resistivity meter (manufactured by Nitto Seiko Analytech Co., Ltd., trade name: “Loresta-AX MCT-T370”) and a four-probe probe (manufactured by Nitto Seiko Analytech Co., Ltd., trade name: “ASP probe MCP-TP03P”) in accordance with JIS K7194. The number of measurement points is set to 1 point, and the resistivity correction factor is 4.532.

[0022] When the heating means is electromagnetic induction heating, the heating element is preferably an electric conducting body having resistance, and examples thereof include metals such as iron, aluminum, nickel, stainless steel, zinc, lead, and magnesium, and oxides and alloys of these metals, etc. Among them, aluminum and iron are preferred.

[0023] When the heating means is infrared heating or microwave heating, the heating element is preferably a substance having the property of absorbing a specific wavelength of infrared heating or microwave heating and thermally vibrating (generating heat), and examples thereof include organic substances and inorganic substances. Examples of organic substances include resins, rubbers, fibers, organic pigments, organic dyes, and organic pigments. Examples of inorganic substances include metal inorganic substances, non-metal inorganic substances, inorganic pigments, inorganic dyes, and inorganic pigments. Examples of metal inorganic substances include non-ferrous metals such as aluminum, titanium, chromium, manganese, cobalt, nickel, magnesium, zinc, and copper; iron; oxides of the non-ferrous metals and iron; and non-metal inorganic substances include silicon, carbon; silicon oxides (e.g., SiO2).

[0024] When the heating means is heat conduction, the heating element is preferably a material with excellent thermal conductivity, for example, metals, non-metals, etc. Examples of metals include aluminum, iron, copper, oxides and nitrides of these metals, etc. Examples of non-metals include ceramics such as silicon carbide, graphite, etc.

[0025] When the heating means is resistance heating, the shape of the heating element is not particularly limited as long as the heating elements are in electrical contact with each other and resistance heating can occur. The shape can be appropriately selected according to the purpose, and examples include planar, mesh, granular, fibrous, etc. Among them, a planar shape is preferred from the perspectives of being able to fully adhere to the molten softened layer in contact with the heating element before power is applied, and being less likely to cause damage or disconnection of the heating element itself when power is applied and disassembled. As planar heating elements, for example, there can be mentioned: metal foil containing the aforementioned metal; the aforementioned non-metallic sheet; a resin film or sheet in which particles or fibers containing the aforementioned metal or the aforementioned non-metal are densely dispersed, such as a metal vapor-deposited film, a woven or non-woven fabric subjected to conductive plating, or a conductive coating film; a coating film of the aforementioned metal or the aforementioned non-metal; a sheet in which the aforementioned metal or the aforementioned non-metal is impregnated in a non-woven fabric; a non-woven fabric of the aforementioned metal or the aforementioned non-metal, such as a metal fiber sheet. Among them, metal foil, non-metallic sheet, metal or non-metallic coating film, and metal or non-metallic non-woven fabric are preferred, and metal foil is more preferred, because the entire surface can be heated and the wire is less likely to break.

[0026] The planar heating element may be formed into a pattern, a strip or a line (see also the following). Figure 4 ). If the heating element is in the form of a strip or line, the heating efficiency is high and the contact area with the adherend is small, so it is advantageous in that it is easy to peel off. In this case, the length of the short axis direction of the heating element (the strip width or the line width) is preferably 0.5 mm to 20 mm, more preferably 1 mm to 10 mm, and further preferably 2 mm to 5 mm.

[0027] If the planar heating element is patterned (having a pattern shape), the distance between the terminals (terminals for connecting to a power source) of the heating element can be extended, and the resistance can be increased. Therefore, the heating efficiency of the planar heating element becomes higher, so that the adhesive tape of the present invention can be peeled off in a short time. The pattern width in the case where the planar heating element is patterned is not particularly limited and can be the same as the preferred range of the above-mentioned tape width.

[0028] In a planar heating element, the heating element may be arranged on one side or both sides of the substrate. In this case, the heating element is arranged in direct contact with one side or both sides of the substrate. In addition, the heating element may be arranged to cover the entire area of ​​one side or both sides of the substrate, or may be arranged in a linear, strip or patterned form. As a substrate, there is no particular limitation as long as it can support the heating element. From the viewpoints of the followability, film formation, heat resistance, etc. of the adhesive tape, polyesters such as polyethylene terephthalate and polyethylene naphthalate; polyolefins such as polypropylene; and films of resins such as polyimide are preferred.

[0029] Examples of the mesh-shaped heating element include a heating element having a plurality of through holes in a planar heating element, a mesh-shaped heating element or a grid-shaped heating element, etc. These may be integrally molded heating elements.

[0030] In addition, the shape of the heating element does not necessarily need to be integrally formed as long as the heating elements can be in electrical contact with each other. For example, the heating element can be particles or fibers containing the metal or the non-metal, or a granular, mesh-shaped, or fibrous heating element can be dispersed in the aforementioned resin film as a substrate to form electrical contact between the heating elements. When a granular, mesh-like or fibrous heating element is dispersed in the aforementioned resin film as a substrate, the content of the granular or fibrous heating element in the resin film as a substrate is preferably 20% to 95% by mass, more preferably 40% to 90% by mass.

[0031] The average thickness of the planar heating element is usually 1 μm or more, preferably 2 μm or more, more preferably 3 μm or more, further preferably 5 μm or more, and particularly preferably 10 μm or more. The average thickness of the planar heating element is preferably 200 μm or less, more preferably 150 μm or less, further preferably 100 μm or less, and particularly preferably 50 μm or less. When the average thickness of the planar heating element is within the above range, sufficient current and heat generation can be obtained, the heating element can be efficiently heated by resistance heating, and excellent followability and sticking workability of the adhesive tape can be obtained. It should be noted that the average thickness of the planar heating element is the average value of the thickness measured at arbitrarily selected 5 or more locations. In the case where the planar heating element is arranged on one or both sides of the substrate, the average thickness of the planar heating element refers to the thickness excluding the substrate, and in the case where the heating element is arranged on both sides of the substrate, it refers to the thickness of the heating element on each single side.

[0032] When the heating means is electromagnetic induction heating or heat conduction, the shape of the heating element can be appropriately selected, for example, it can be planar, it can also be mesh-shaped, or it can be a resin film or sheet in which particles or fibers containing the heating element are densely dispersed. The planar heating element can be formed into a pattern, or it can be strip-shaped or linear. If the heating element is strip-shaped or linear, the heating efficiency is high, and the contact area with the adherend is small, so it is easy to peel off. The length of the short axis direction of the heating element (band width or line width) is preferably 1mm to 10mm, and more preferably 2mm to 5mm. The average thickness of the planar heating element is preferably 5μm to 200μm, more preferably 10μm to 150μm, and further preferably 12μm to 100μm.

[0033] When the heating means is infrared heating or microwave heating, the heating element may be a resin film or sheet in which particles or fibers containing the heating element are dispersed at a high density. When the heating means is infrared heating, a pigment or the like may be used as an infrared absorbing material, and the pigment may be dispersed in the resin film or sheet, or may be coated on the resin film or sheet by coating or the like.

[0034] The heating element can be manufactured appropriately, or commercial products can be used. Examples of commercial products include planar heating elements such as nickel-chromium alloy foils such as "NCH1-H", "SUS304-H", "SUS430-H", "TR270C-H", and "Nanosilver C7701" (all manufactured by Takeuchi Metal Foil Co., Ltd.); and "stainless steel fiber sheets" manufactured by Tomogawa Paper Co., Ltd. In addition, heating elements formed by patterning these materials can also be used.

[0035] [Adhesive layer] In the adhesive tape of the present invention, the components constituting the adhesive layer include, for example, acrylic adhesives, urethane adhesives, rubber adhesives such as synthetic rubber or natural rubber, silicone adhesives, vinyl ether adhesives, etc. Among them, adhesives that can be used as pressure-sensitive adhesives are preferred, and acrylic adhesives containing acrylic polymers are more preferred. Acrylic adhesives containing acrylic polymers are not easy to melt or soften due to heating. Therefore, the heat generated by the heating element of the adhesive tape of the present invention can selectively melt or soften the melt-softening layer possessed by the adhesive tape of the present invention. It should be noted that a pressure-sensitive adhesive refers to an adhesive that is bonded by applying pressure for a short time at room temperature near 20°C and has viscosity at room temperature.

[0036] Examples of acrylic polymers include homopolymers of (meth)acrylate monomers, copolymers of (meth)acrylate monomers and other monomers, and the like. In this specification, "(meth)acrylic acid" is a general term for acrylic acid, methacrylic acid, and both of them. "(Meth)acrylate" is a general term for acrylate, methacrylate, and both of them.

[0037] Examples of the (meth)acrylate monomer include alkyl (meth)acrylates having an alkyl chain having 1 to 14 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, and lauryl (meth)acrylate. The acrylic polymer may contain one kind of these monomers in a structural unit, or may contain two or more kinds of them in a structural unit.

[0038] The content of the (meth)acrylate monomer is preferably 70 to 99.9% by mass, more preferably 80 to 99% by mass, and even more preferably 90 to 97% by mass, based on all monomer components constituting the acrylic polymer.

[0039] Furthermore, as other monomers for obtaining the acrylic polymer, a polar group-containing monomer may be contained. Examples of the polar group-containing monomer include carboxylic acids having an ethylenically unsaturated group, such as (meth)acrylic acid, itaconic acid, itaconic anhydride, maleic acid, maleic anhydride, and crotonic acid; (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified (meth)acrylate, polyoxyethylene (meth)acrylate, and polyoxypropylene (meth)acrylate; and nitrogen-containing monomers having an ethylenically unsaturated group, such as (meth)acrylonitrile, N-vinyl-2-pyrrolidone, N-vinylcaprolactam, N-vinyllaurolactam, (meth)acryloylmorpholine, (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, N,N-dimethylaminomethyl (meth)acrylate, and 2-(perhydrophthalimide-N-yl)ethyl acrylate.

[0040] When a cross-linking agent described later is used in combination, from the viewpoint of being able to form a cross-linked structure between the hydroxyl group, the carboxyl group and the cross-linking agent and being able to adjust the storage modulus of the adhesive layer, the polar group-containing monomer is preferably a (meth)acrylate having a hydroxyl group, a carboxylic acid having an ethylenically unsaturated group, and more preferably 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, or acrylic acid.

[0041] The content of the polar group-containing monomer in the acrylic polymer is preferably in the range of 0.1 to 20 mass %, more preferably 1 to 13 mass %, and even more preferably 1.5 to 8 mass %, relative to all components of the monomers constituting the acrylic polymer.

[0042] The weight average molecular weight of the acrylic polymer is preferably in the range of 400,000 to 1,400,000, more preferably in the range of 600,000 to 1,200,000, and even more preferably in the range of 650,000 to 1,100,000. Here, the weight average molecular weight is a weight average molecular weight in terms of standard polystyrene measured by gel permeation chromatography (GPC). Specifically, as a GPC measuring apparatus, "SC8020" manufactured by Tosoh Corporation is used and the measurement is determined under the following measurement conditions. Sample concentration: 0.5 mass% (tetrahydrofuran solution) Sample injection volume: 100μL ·Eluent: Tetrahydrofuran (THF) Flow rate: 1.0mL / min Column temperature (measurement temperature): 40°C Column: "TSKgel GMHHR-H" manufactured by Tosoh Corporation Detector: Differential refractometer

[0043] For the purpose of adjusting its adhesiveness, the adhesive layer may further contain a tackifying resin. As the tackifying resin, for example, various tackifying resins such as rosin, polymerized rosin, polymerized rosin ester, rosin phenol, stabilized rosin ester, disproportionated rosin ester, hydrogenated rosin ester, terpene, terpene phenol, petroleum resin, C5 / C9 petroleum resin, (methyl) acrylate can be cited. In addition, tackifying resins that are liquid at room temperature such as low molecular weight liquid rubbers such as process oil, polyester tackifying resins, and polybutene can also be used. In the case where the adhesive layer contains a tackifying resin, from the viewpoint of making the adhesive property near room temperature (0 to 40° C.) good and being able to exert thermal durability, the amount of the tackifying resin is preferably in the range of 1 to 150 parts by mass, more preferably in the range of 10 to 150 parts by mass, relative to 100 parts by mass of the base resin such as the acrylic polymer constituting the adhesive layer. In addition, in the case where the adhesive layer contains a tackifying resin, the total content of the base resin and the tackifying resin in the adhesive forming the adhesive layer is preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 90% by mass or more, relative to the total solid content of the adhesive.

[0044] For the purpose of improving the cohesive force, the adhesive layer may further contain a crosslinking agent. Examples of the crosslinking agent include isocyanate-based, epoxy-based, aziridine-based, polyvalent metal salt-based, metal chelate-based, ketone-hydrazine-based, oxazoline-based, carbodiimide-based, silane-based, glycidyl (alkoxy) epoxy silane-based and other known crosslinking agents.

[0045] The adhesive layer may further contain other additives such as antioxidants, anti-aging agents, colorants such as pigments and dyes, thickeners, leveling agents, film-forming aids, infrared absorbers, ultraviolet absorbers, and water repellents as needed within a range that does not impair the effects of the present invention.

[0046] The adhesive layer may further include a thermoplastic resin. In the adhesive tape of the present invention, from the viewpoint of selectively melting or softening the melt-softening layer by utilizing the heat generated by the heating element, it is preferably composed of a component that is different from the thermoplastic resin contained in the melt-softening layer and is not easily melted or softened by heating. More specifically, for example, a preferred embodiment is a thermoplastic resin that has a loss tangent (tan δ) of 0.8 or more in a temperature range of 40°C or more, which is higher than the temperature at which the tan δ of the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softening layer described later reaches 0.8 or more. It should be noted that, hereinafter, “the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softening layer” is also simply referred to as “melt-softening resin composition.” The melt-softening resin composition will be described in detail later.

[0047] From the viewpoint of adhesion holding power to the adherend and film uniformity during solution coating, the thickness of the adhesive layer is preferably in the range of 10 to 200 μm, more preferably in the range of 20 to 100 μm. The thickness of the adhesive layer is the average value of thicknesses measured at any five locations.

[0048] The melting point of the adhesive layer is preferably higher than the melting point of the melt-softening layer described later. Here, the "melting point of the adhesive layer" refers to the melting point of a composition (hereinafter referred to as "adhesive layer composition") consisting of an acrylic adhesive, a urethane adhesive, a rubber adhesive, a silicone adhesive, a vinyl ether adhesive, etc., which constitute the adhesive layer, and a tackifying resin, a crosslinking agent, other additives, and a thermoplastic resin different from the thermoplastic resin contained in the melt-softening layer as required. The melting point of the adhesive layer (adhesive layer composition) is preferably above 130°C, and more preferably in the range of 130°C to 200°C. By adjusting the melting point of the adhesive layer to the above range and adjusting the melting point of the melt-softening layer to the range described later, the heat generated by the heating element can be used to cause the melting or softening of the melt-softening layer to occur before the melting or softening of the adhesive layer. That is, when an article having a structure bonded by the adhesive tape of the present invention is thermally disassembled, the melting or softening of the melt-softening layer can be stably and preferentially occurred, and it can be easily disassembled. In addition, the "melting point of the adhesive layer" is the temperature of the endothermic peak accompanying the melting of the adhesive layer (adhesive layer composition) measured by differential scanning calorimetry (DSC).

[0049] In the temperature range of 40°C or more, the temperature at which the tanδ of the adhesive layer (adhesive layer composition) reaches 0.8 or more is preferably higher than the temperature at which the tanδ of the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softening layer (i.e., the melt-softening resin composition described later) reaches 0.8 or more. Among them, the temperature at which the tanδ of the adhesive layer (adhesive layer composition) reaches 0.8 or more is more preferably higher than the temperature at which the tanδ of the melt-softening resin composition reaches 1 or more. Specifically, within the temperature range of 40°C or above, the temperature at which the tan δ of the adhesive layer (adhesive layer composition) reaches 0.8 is preferably higher than the temperature at which the tan δ of the melt-softening resin composition is 0.8, more preferably higher than the temperature at which the tan δ of the melt-softening resin composition is 1, and further preferably higher than the temperature at which the tan δ of the melt-softening resin composition is 1.2.

[0050] As one of the preferred aspects of the adhesive layer (adhesive layer composition), the maximum value of tanδ in the temperature range of 80°C to 160°C is preferably less than 1, more preferably less than 0.8, and further preferably less than 0.6. From the viewpoint that the adhesive layer can exert viscosity and elasticity, the tanδ of the adhesive layer (adhesive layer composition) in the temperature range of 80°C to 160°C is preferably 0.2 or more.

[0051] As one preferred embodiment of the adhesive layer, the temperature range in which tan δ of the adhesive layer (adhesive layer composition) reaches 0.8 or more is preferably higher than 150° C., more preferably higher than 170° C. The upper limit of the temperature range is not particularly limited, and can be, for example, 300° C., preferably 250° C. In the adhesive tape of the present invention, if the adhesive layer has such physical properties, when the adhesive layer and the melt-softening layer receive the same heat from the heating element, the melting and / or softening of the adhesive layer can be suppressed. That is, when the article having the structure bonded by the adhesive tape of the present invention is thermally disassembled, the melting or softening of the melt-softening layer can be stably and preferentially caused while the melting or softening of the adhesive layer is suppressed, and the article can be easily disassembled in a short time. In addition, from the viewpoint of being able to exhibit good adhesion to the adherend before and after detachment, the tan δ of the adhesive layer (adhesive layer composition) at 23°C is preferably 0.1 to 0.8, more preferably 0.2 to 0.6.

[0052] The tanδ of the adhesive layer (adhesive layer composition) is obtained by measuring the dynamic viscoelasticity at a frequency of 1 Hz. For example, a test piece of the adhesive layer composition with a dry thickness of about 2 mm is prepared, and a viscoelasticity tester (ARES-G2, manufactured by TA Instruments Japan Co., Ltd.) is used to measure the storage modulus G' and loss modulus (G") under the conditions of a frequency of 1 Hz, a temperature range of -40°C to 200°C, and a heating rate of 2°C / min. Tanδ can be calculated by the calculation formula [tanδ = G" / G'].

[0053] The tanδ of the adhesive layer (adhesive layer composition) can be adjusted by the type of monomers constituting the base polymer of the adhesive as the main component, such as the above-mentioned acrylic polymer, the combination and the mixing ratio of various monomers, the mixing amount of the tackifier resin added as needed, the addition amount of the cross-linking agent added as needed (gel fraction), etc.

[0054] 〔Melted softened layer〕 The melt-softened layer constituting the adhesive tape of the present invention contains a thermoplastic resin and an inorganic hollow filler. <Inorganic hollow fillers> As inorganic hollow fillers, for example, metal oxide ceramics such as aluminum oxide, silicon dioxide, aluminum silicate (silica alumina), zirconium oxide, magnesium oxide, etc. can be cited; non-oxide ceramics such as silicon carbide, boron carbide, nitrogen carbide, aluminum nitride, silicon nitride, boron nitride, etc.; hollow fillers containing inorganic substances such as glass, calcium carbonate, volcanic ash (white sand (Japanese: シラス)), fly ash (fly ash). They can be used alone or in combination of two or more. In addition, the inorganic hollow filler can be surface treated by hydrophobization using silane coupling agents, fluorine compounds, etc.

[0055] Among the above, from the viewpoint that the melt-softening layer constituting the adhesive tape of the present invention exerts an insulating effect of suppressing the conduction of heat generated by the heating element to the adherend while maintaining the characteristics such as shear force and holding force, and from the viewpoint of being able to further exert the heat storage effect of the melt-softening layer, it is preferred to use at least one inorganic hollow filler selected from glass hollow fillers and silica hollow fillers, and more preferably a glass hollow filler. Inorganic hollow fillers containing glass are commercially available, for example, the "Glass Bubbles" series (trade name; manufactured by 3M Company); the "Q-CEL (registered trademark)" series, the "Sphericel (registered trademark)" series (all manufactured by Potters-Ballotini Co., Ltd.); and the "Glass Balloon" (trade name; manufactured by Bass Industries Co., Ltd.).

[0056] From the viewpoint of easily maintaining the strength of the melt-softening layer in the bonded state and making the heat storage effect of the melt-softening layer better, the particle size (average particle size) of the inorganic hollow filler is preferably less than the thickness of the melt-softening layer, preferably in the range of 1 μm to 500 μm, preferably in the range of 1 μm to 200 μm, more preferably in the range of 5 μm to 200 μm, more preferably in the range of 10 μm to 100 μm, and further preferably in the range of 10 μm to 80 μm. In addition, the particle size of the inorganic hollow filler is a value of a median particle size (D50) measured by a laser diffraction / scattering particle size distribution analyzer.

[0057] The specific gravity (true density) of the inorganic hollow filler is preferably 0.01 g / cm2 in general, from the viewpoint of improving the dispersibility of the inorganic hollow filler in the melt-softened layer and not excessively increasing the mass of the pressure-sensitive adhesive tape of the present invention. 3 ~1.8g / cm 3 The range is more preferably 0.02 g / cm 3 ~1.5g / cm 3 range.

[0058] The amount of the inorganic hollow filler is preferably in the range of 5% to 80% by volume relative to the total volume of the melt-softening layer, and more preferably in the range of 10% to 65% by volume. In addition, the amount of the inorganic hollow filler is preferably in the range of 0.1% to 80% by volume relative to the total mass of the melt-softening layer, and more preferably in the range of 1.0% to 70% by volume. If the amount of the inorganic hollow filler in the melt-softening layer is in the range described above, it is advantageous from the viewpoint of improving the heat insulation effect of the melt-softening layer and being able to further exert its heat storage effect.

[0059] The inorganic hollow filler is preferably a filler that is not easily expanded or foamed by heating and whose volume does not substantially increase by heating. The expansion ratio (volume ratio) after heating at 120° C. to 160° C. for 5 minutes is preferably 1.5 times or less, more preferably 1.2 times or less.

[0060] <Thermoplastic resin> As thermoplastic resin, for example, crystalline or amorphous polyester resins such as carbamate resins, polycarbonate, vinyl chloride resins, acrylic resins, polyethylene terephthalate, polyamide resins, styrene resins, olefin resins, cellulose resins, silicone resins, fluorine resins, styrene thermoplastic elastomers, olefin thermoplastic elastomers, vinyl chloride thermoplastic elastomers, acrylic thermoplastic elastomers, carbamate thermoplastic elastomers, ester thermoplastic elastomers, amide thermoplastic elastomers, etc. can be mentioned. These can be used alone or in combination of two or more. From the viewpoint that the adhesive tape of the present invention can be melted or softened under the action of the heat generated by the heating element, and that the melt-softened layer can be melted or softened even without containing components such as heating foaming agents that produce a peeling starting point at the bonding interface and components that cause a decrease in adhesion, thereby enabling the adhesive tape to be peeled; and from the viewpoint that it preferably has a softening point and that the melt-softened layer becomes soft rapidly by reaching a temperature higher than the softening point, thereby facilitating the expression of high deformability and fluidity, the thermoplastic resin is preferably a carbamate resin, an acrylic resin, a polyester resin, a styrene thermoplastic elastomer, an olefin thermoplastic elastomer, a vinyl chloride thermoplastic elastomer, an acrylic thermoplastic elastomer, a carbamate thermoplastic elastomer, an ester thermoplastic elastomer, and an amide thermoplastic elastomer, and a styrene thermoplastic elastomer is more preferred.

[0061] As the styrene-based thermoplastic elastomer, a block copolymer or a hydrogenated product thereof is preferably a block copolymer, wherein the block copolymer comprises: a polymer block containing a structural unit derived from an aromatic vinyl compound and a polymer block containing a structural unit derived from a conjugated diene compound. Specifically, examples thereof include: a polystyrene-polybutadiene diblock copolymer or a polystyrene-poly(ethylene-butylene) diblock copolymer (SEB) as a hydrogenated product thereof, a polystyrene-polybutadiene-polystyrene triblock copolymer (SEB) or a polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer (SEBS) as a hydrogenated product thereof, a polystyrene-polyisoprene diblock copolymer or a polystyrene-poly(ethylene-propylene) diblock copolymer (SEP) as a hydrogenated product thereof, a polystyrene-polyisoprene - Polystyrene triblock copolymer (SIS) or its hydrogenated product, polystyrene-poly(ethylene-propylene)-polystyrene triblock copolymer (SEPS), polystyrene-polybutadiene-polystyrene-polybutadiene tetrablock copolymer (SBSB) or its hydrogenated product, polystyrene-polybutadiene-polystyrene-polybutadiene-polystyrene pentablock copolymer (SBSBS), styrene-based multiblock copolymers, hydrogenated products of styrene-based random copolymers such as styrene-butadiene rubber (SBR) after hydrogenation of ethylene-type double bonds, etc. Moreover, as a styrene-based thermoplastic elastomer, a commercial item can also be used.

[0062] The weight average molecular weight of the styrene-based thermoplastic elastomer is preferably in the range of 10,000 to 800,000, more preferably in the range of 30,000 to 500,000, and further preferably in the range of 50,000 to 300,000. If the weight average molecular weight is set to the above range, it is easy to adjust the storage modulus and loss tangent of the melt-softened layer to the desired range, and the melting or softening of the melt-softened layer by heating becomes easy. It should be noted that the weight average molecular weight of the styrene-based thermoplastic elastomer is obtained in the same manner as the determination method of the weight average molecular weight of the acrylic polymer.

[0063] The styrene-based thermoplastic elastomer may be used alone or in combination of two or more. That is, the styrene-based thermoplastic elastomer may be one or more triblock copolymers, one or more diblock copolymers, or a mixture of a triblock copolymer and a diblock copolymer. Among them, the styrene-based thermoplastic elastomer preferably contains at least a diblock copolymer from the viewpoint that the melt-softened layer shows moderate cohesive force, has good adhesive force near room temperature (0°C to 40°C) before heating, and can be easily melted or softened by heating. The content of the diblock copolymer in the styrene-based thermoplastic elastomer is preferably in the range of 10% to 100% by mass, more preferably in the range of 10% to 90% by mass, and further preferably in the range of 15% to 80% by mass; from the viewpoint of excellent balance between adhesiveness at 20°C and meltability based on heating, it is particularly preferably in the range of 20% to 75% by mass.

[0064] The melt-softening layer is melted or softened by the heat generated by the heating element, whereby the adhesive force during heating is lower than the adhesive force at around room temperature (0° C. to 40° C.). The content of the thermoplastic resin in the melt-softening layer is preferably in the range of 30% to 95% by mass, more preferably in the range of 35% to 90% by mass, relative to the total amount of the melt-softening layer. If the amount of the thermoplastic resin in the melt-softening layer is in the above range, it is advantageous from the viewpoint of controlling the coating properties and melt-softening temperature of the melt-softening layer.

[0065] <Optional ingredients> In addition to the above-mentioned inorganic hollow fillers, the melt-softening layer may also include an organic hollow filler that does not expand or foam due to heating. The organic hollow filler has a hollow structure in which the outer shell is made of resin and the central part is hollow. As an organic hollow filler that does not expand or foam due to heating, for example, an expanded organic hollow filler and a foamed organic hollow filler can be cited. Such an organic hollow filler can play the same heat storage effect of the melt-softening layer as the above-mentioned inorganic hollow filler, and the heat insulation effect of suppressing the conduction of heat generated by the heating element to the adherend. It should be noted that the organic hollow filler that does not expand or foam due to heating refers to an organic hollow filler whose volume does not substantially increase due to heating, and the expansion rate (volume ratio) after heating at 120°C to 160°C for 5 minutes is preferably 1.5 times or less, and more preferably 1.2 times or less. Examples of the resin constituting the organic hollow filler include resins containing structural units derived from acrylonitrile, vinyl chloride, vinylidene chloride, styrene, vinyl acetate, ethylene, (meth)acrylate, etc. Examples include acrylonitrile polymers, vinylidene chloride polymers, acrylic polymers, styrene polymers, polyethylene polymers, etc.

[0066] The organic hollow filler that can be contained in the melt-softening layer is preferably a filler that will not expand or foam due to heating, but in the scope of not hindering the effect of the present invention, it is also possible to contain a small amount of organic hollow filler (thermally expansive organic hollow filler or thermally foamable organic hollow filler) that expands or foams due to heating. The melt-softening layer may not substantially include the organic hollow filler that expands or foams by heating. So-called "substantially not including" refers to, for example, relative to 100 mass parts of melt-softening resin composition, the amount of thermally expansive organic hollow filler or thermally foamable organic hollow filler is less than 10 mass parts, preferably less than 5 mass parts, more preferably less than 1 mass part, further preferably less than 0.5 mass part, particularly preferably 0 mass part.

[0067] The melt-softened layer may further contain a tackifier resin for the purpose of adjusting its adhesiveness. The details of the tackifier resin are the same as those of the tackifier resin described in the item of the adhesive layer. The melt-softened layer may further contain a crosslinking agent for the purpose of improving cohesive force. The details of the crosslinking agent are the same as those of the crosslinking agent described in the item of the adhesive layer. The melt-softened layer may further contain other additives such as antioxidants, anti-aging agents, colorants such as pigments and dyes, thickeners, leveling agents, film-forming aids, infrared absorbers, ultraviolet absorbers, and water repellents as needed within a range that does not impair the effects of the present invention. In the case where the melt-softening layer contains a tackifying resin, from the viewpoint of making it have good adhesion near room temperature (0 to 40° C.) and being able to exert thermal durability, the amount of the tackifying resin is preferably in the range of 1 to 150 parts by mass, and more preferably in the range of 10 to 150 parts by mass, relative to 100 parts by mass of the thermoplastic resin constituting the melt-softening layer. In addition, in the case where the melt-softening layer contains a tackifying resin, the total content of the thermoplastic resin and the tackifying resin constituting the melt-softening layer is preferably in the range of 20% to 99.9% by mass, and more preferably in the range of 30% to 99.0% by mass, relative to the total mass of all the components constituting the melt-softening layer, i.e., the inorganic hollow filler, the thermoplastic resin and the tackifying resin, and any cross-linking agent and other additives contained.

[0068] <Physical properties of melt-softened layer> The melting point of the melt-softening layer is preferably lower than the melting point of the adhesive layer. Specifically, it is preferably in the range of 80°C to 200°C, more preferably in the range of 90°C to 180°C, and further preferably in the range of 100°C to 160°C. Here, the "melting point of the melt-softening layer" refers to the melting point of the composition (i.e., the melt-softening resin composition) formed by the components of the melt-softening layer, excluding the inorganic hollow filler, and containing the thermoplastic resin. In other words, the melt-softening resin composition refers to a composition containing the thermoplastic resin constituting the melt-softening layer, excluding the inorganic hollow filler, and further containing a tackifying resin, a cross-linking agent, other additives, etc. as needed. The "melting point of the melt-softening layer" refers to the melting point of the melt-softening resin composition. If the melting point of the melt-softening layer is within the above range, the adhesive tape of the present invention can exert high adhesive force before heating. Furthermore, when the articles having the structure bonded by the adhesive tape of the present invention are thermally disassembled, even if the amount of heating caused by the heat generated by the heating element is small, the melt-softening layer can be melted or softened stably and preferentially, and can be easily disassembled in a short time. In addition, the "melting point of the melt-softening layer" is the temperature of the endothermic peak accompanying the melting of the melt-softening resin composition measured by differential scanning calorimetry (DSC).

[0069] From the viewpoint of well fixing adherends to each other at room temperature (0°C to 40°C), the storage modulus G of the melt-softened resin composition at 23°C is 23 Preferably 1.0×10 3 Pa~1.0×10 9 Pa, more preferably 1.0×10 3 Pa~5.0×10 7 Pa, more preferably 5.0×10 3 Pa~5.0×107 Pa, more preferably 5.0×10 3 Pa~5.0×10 6 Pa, particularly preferably 5.0×10 3 Pa~1.0×10 6 Pa. From the viewpoint of making it easy to separate adherends by heating, the storage modulus G of the melt-softened resin composition at 120°C is 120 Preferably 1.0×10 0 Pa~5.0×10 6 Pa, more preferably 1.0×10 3 Pa~1.0×10 6 Pa, more preferably 1.0×10 3 Pa~1.0×10 6 Pa, more preferably 5.0×10 3 Pa~5.0×10 5 Pa. If the storage modulus G 120 When the content is within the above range, the melt-softening layer can be melted or softened in a short time by heating and can be peeled off.

[0070] The melt-softened resin composition preferably has a tan δ in a temperature range of 80° C. or higher (preferably a tan δ in a temperature range of 100° C. or higher) of 0.8 or higher, and more preferably 1 or higher. As one of the preferred aspects of the melt-softening layer, the temperature at which the tan δ of the melt-softening resin composition reaches 0.8 or more is preferably lower than the temperature at which the tan δ of the adhesive layer (adhesive layer composition) reaches 0.8 or more. Specifically, the temperature range at which the tan δ of the melt-softening resin composition reaches 0.8 or more is, for example, preferably 80°C or more, more preferably 80°C or more and 200°C or less, further preferably 100°C or more and 160°C or less, and further preferably 100°C or more and 130°C or less. More specifically, the temperature at which the tan δ of the melt-softened resin composition reaches 0.8 is preferably 80°C or higher, more preferably 80°C or higher and 200°C or lower, further preferably 100°C or higher and 160°C or lower, and further preferably 100°C or higher and 130°C or lower. The temperature at which tan δ of the melt-softened resin composition reaches 1 is preferably 80°C or higher, more preferably 80°C or higher and 200°C or lower, further preferably 100°C or higher and 180°C or lower, and still further preferably 100°C or higher and 130°C or lower.

[0071] The difference between the temperature at which the tan δ of the melt-softening resin composition reaches 0.8 (more preferably the temperature at which the tan δ reaches 1) and the temperature at which the tan δ of the adhesive layer (adhesive layer composition) reaches 0.8 (more preferably the temperature at which the tan δ reaches 1) can be a temperature difference that allows the melt-softening layer to preferentially melt or soften by receiving heat from the heating element, and is, for example, 10°C or more, preferably 25°C or more, further preferably 30°C or more, and more preferably 50°C or more. In the adhesive tape of the present invention, if the melt-softening resin composition has such a physical property, when the adhesive layer and the melt-softening layer receive the same heat from the heating element, the melting and / or softening of the melt-softening layer is likely to occur preferentially. When the melt-softening layer reaches the desired disassembly temperature range described later by the heat generated by the heating element, it is easy to produce plastic deformation due to melting or softening, and through cohesive failure in the melt-softening layer, it can be peeled off in the layer of the melt-softening layer, or at the interface of the layer adjacent to the melt-softening layer or the adherend. That is, when the article having the structure bonded by the adhesive tape of the present invention is thermally disassembled, the melting or softening of the melt-softening layer can be stably and preferentially occurred, and it can be easily disassembled in a short time. In addition, from the viewpoint of improving the adhesiveness before disassembly, the tan δ of the melt-softened resin composition at 23°C is preferably 0.1 to 0.8, and more preferably 0.2 to 0.6.

[0072] It should be noted that the storage modulus G and tanδ of the components (melt-softening resin composition) containing thermoplastic resins other than inorganic hollow fillers constituting the melt-softening layer are determined by dynamic viscoelasticity measurement. For example, a test piece of a melt-softening resin composition having a dry thickness of about 2 mm is prepared, and a viscoelasticity tester (ARES-G2, manufactured by TA Instruments Japan Co., Ltd.) is used to measure the storage modulus G' and loss modulus (G") at each temperature under the conditions of a frequency of 1 Hz, a temperature range of -40°C to 200°C, and a heating rate of 2°C / min. Tanδ can be calculated by the calculation formula [tanδ=G" / G'].

[0073] Storage modulus G of melt-softened resin composition 23 , Storage modulus G 120 , tan δ and melting point can be adjusted by the type and combination of thermoplastic resins, the amount of tackifier resin added as needed, the amount of crosslinking agent added as needed, and the like.

[0074] The thermal conductivity of the melt-softening layer is preferably in the range of 0.03 W / m·K to 0.20 W / m·K, more preferably in the range of 0.03 W / m·K to 0.18 W / m·K, and further preferably in the range of 0.05 W / m·K to 0.15 W / m·K. If the thermal conductivity is within the above range, the heat generated by the heating element will not be transferred to the adherend but will be easily stored in the melt-softening layer, so that the melt-softening layer can be melted or softened in a short time, and thus can be easily disassembled. The thermal conductivity of the melt-softened layer can be measured, for example, using a rapid thermal conductivity meter ("QTM-710" manufactured by Kyoto Electronics Co., Ltd.).

[0075] From the viewpoint of coating property, adhesive retention force to adherend, and disassembly property, the thickness of the melt-softened layer can be set to 500 μm or less, preferably in the range of 10 μm to 200 μm, and more preferably in the range of 20 μm to 150 μm. It should be noted that the thickness of the melt-softened layer is set to the average value obtained by measuring the thickness at any 5 locations.

[0076] The adhesive tape of the present invention has at least one melt-softening layer adjacent to the heating element, and may also have a melt-softening layer c1 adjacent to one side of the layered heating element and a melt-softening layer c2 adjacent to the other side of the heating element. The specific layer structure of the adhesive tape having two melt-softening layers will be described later.

[0077] [Layer Structure of Adhesive Tape] The first embodiment of the adhesive tape of the present invention is as follows Figure 1 and Figure 2 As shown, the adhesive tape 10 may be a laminated body having a planar heating element b, an adhesive layer a disposed on one side of the planar heating element b, and a melt-softening layer c disposed on the other side of the planar heating element b, and laminated in the order of adhesive layer a / heating element b / melt-softening layer c. The melt-softening layer c adjacent to the heating element b melts or softens due to the heat generated by the heating element b, and the adhesive force is reduced, making it possible to peel off.

[0078] The planar heating element b preferably has a pair of protruding portions e extending and exposed from the periphery of the adhesive layer a and the melt-softened layer c in a plan view (see Figure 3 and Figure 4 The extensions e may be independently located at two or more locations. There is no particular limitation on the location of the extensions e in the heating element and the extensions e may be appropriately selected according to the purpose. The two extensions e may be located on the same side of the periphery of the adhesive layer a and the melt-softening layer c (see Figure 4 (1) to (3)), they can also be located on two different sides (see Figure 3 , Figure 4 (4)~(6)).

[0079] The extension portion e is preferably located on two opposite sides of the periphery of the adhesive layer a and the melt-softened layer c (see Figure 4 (4) to (6)), preferably located on the substantially diagonal lines of the peripheries of the adhesive layer a and the melt-softened layer c (see Figure 4 (2) to (7)). In addition, when the extension portion e is located on the same side of the periphery of the adhesive layer a and the melt-softening layer c, it is preferred that the heating element b is in a U-shape or a sawtooth shape in a top view (see Figure 4 (1) to (4), (8)), as long as the heating element b can uniformly heat the adhesive layer a and the melt-softened layer c, they may be located in close proximity on the same side (see Figure 4 (3), (8)). This allows current to flow through the entire area of ​​the planar heating element b, and can further improve the heating efficiency.

[0080] The number of the extensions e may be more than 3 (see Figure 4 (9)), a desired pair (2 places) may be appropriately selected to energize the heating element. The pair of extensions e of the heating element b functions as a pair of terminals for electrical connection to a power source in the method for disassembling the article described later, and can easily energize the heating element b.

[0081] From the viewpoint of easy contact with the power source and the heat generating source, the length of the extension is preferably 1 mm to 50 mm, and more preferably 2 mm to 25 mm. Each extension can be bent in a direction different from the surface direction of the adhesive tape. For example, when the adherends are bonded to each other, the extension is bent and stored in a direction perpendicular to the surface direction of the adhesive tape; when the adherends are to be released from bonding (disassembly), the extension is bent again in the surface direction so that the extension is in contact with the power source and the heat generating source.

[0082] In addition, as a second embodiment of the adhesive tape of the present invention, Figure 5 As shown, the adhesive tape 20 may be a laminated body laminated in the order of adhesive layer a1 / heating element b / melt-softening layer c / adhesive layer a2. Alternatively, the adhesive tape 20 may be a laminated body laminated in the order of adhesive layer a1 / melt-softening layer c1 / heating element b / melt-softening layer c2, and in this case, the adhesive layer a2 may be further provided on the side of the melt-softening layer c2 opposite to the heating element b side. That is, as a second embodiment of the adhesive tape of the present invention, there can be cited a laminate having a heating element b, an adhesive layer a1 disposed on one surface of the heating element b, a melt-softening layer c disposed on the other surface of the heating element b, and an adhesive layer a2 located on a surface of the melt-softening layer c that is different from the adjacent surface of the heating element b. In addition, as another example of the second embodiment, there can be cited a laminate having a heating element b, a melt-softening layer c1 and a melt-softening layer c2 disposed on both surfaces of the heating element b, an adhesive layer a1 disposed on a surface of the melt-softening layer c1 that is different from the adjacent surface of the heating element b, and an adhesive layer a2 disposed on a surface of the melt-softening layer c2 that is different from the adjacent surface of the heating element b. The heat generated by the heating element b melts or softens the melt-softening layer c1 or c2 adjacent to the heating element b, and the adhesive force is reduced, making it possible to peel off. The adhesive tape of the present invention in the second mode, in which an adhesive layer is further provided on the surface (opposite surface) of the melt-softening layer different from the adjacent surface of the heating element, can improve the initial adhesive force, and the reduction rate of the adhesive force caused by heating becomes larger. Preferably, in the top view, the planar heating element b has a pair of extensions extending and exposed from the periphery of the adhesive layer a1, the adhesive layer a2 and the melt-softened layer c. The details of the extensions are the same as those of the planar heating element b in the first embodiment.

[0083] The adhesive tape of the present invention may have a release layer (also referred to as a release sheet or a release liner). Examples of the release layer include: glass paper; kraft paper; clay coated paper; paper laminated with a film such as polyethylene; paper coated with a resin such as polyvinyl alcohol or an acrylate copolymer; synthetic resin films such as polyester or polypropylene coated with a fluororesin or a silicone resin, etc. The release layer may be present on one side of the adhesive tape of the present invention or on both sides.

[0084] In the adhesive tape of the present invention, as long as the outermost layer (excluding the peeling layer) located in the thickness direction has an adhesive surface that can be bonded to the adherend, in addition to the adhesive layer, the heating element, and the melt-softening layer, it can also have other layers such as an insulating layer, a heat-insulating layer (for example, a foamed resin layer, a hollow layer, and a hollow particle layer, etc.) and other functional layers having functions such as insulation, heat insulation, or heat insulation.

[0085] The adhesive layer a and the melt-softened layer c in the first embodiment of the adhesive tape of the present invention may be the adhesive surface to the adherend, and the adhesive layer a1 and the adhesive layer a2 in the second embodiment may be the adhesive surface to the adherend. In the second embodiment, the initial adhesive force can be further improved.

[0086] The pressure-sensitive adhesive tape of the present invention can have the following exemplary configurations, but is not limited thereto. " / " in the following laminated structure represents a laminated interface, and for example "layer A / layer B" means that layer A and layer B are adjacent to each other, that is, in direct contact. ·Peeling layer / adhesive layer a / heat generating element b / melting softening layer c Adhesive layer a / heating element b / melting softening layer c / peeling layer ·Peeling layer / adhesive layer a / heat generating element b / melting softening layer c / peeling layer Adhesive layer a / Functional layer / Heat generating element b / Melting softening layer c / Peeling layer ·Peeling layer / adhesive layer a / functional layer / heat generating element b / melting softening layer c / peeling layer ·Peeling layer / adhesive layer a / heat generating element b / melt softening layer c / adhesive layer a Adhesive layer a / heating element b / melting softening layer c / adhesive layer a / peeling layer ·Peeling layer / adhesive layer a / heat generating element b / melting softening layer c / adhesive layer a / peeling layer ·Peeling layer / adhesive layer a / heat generating element b / melt softening layer c / functional layer / adhesive layer a ·Peeling layer / adhesive layer a / functional layer / heat generating element b / melting softening layer c / adhesive layer a / peeling layer ·Peeling layer / adhesive layer a / functional layer / heat generating element b / melt softening layer c / functional layer / adhesive layer a / peeling layer ·Peeling layer / adhesive layer a / melting softening layer c / heat generating element b / melting softening layer c / peeling layer

[0087] The overall thickness of the adhesive tape of the present invention is preferably in the range of 50 μm to 2000 μm, more preferably in the range of 50 μm to 1000 μm, and further preferably in the range of 50 μm to 800 μm. In this case, when adherends are joined to each other, in addition to being able to impart cushioning properties (flexibility) and other effects, the operability of the adhesive tape, such as mechanical strength and processability, can also be further improved.

[0088] [Application of adhesive tape] The two sides of the adhesive tape of the present invention, except for the release layer, function as surfaces with adhesiveness (adhesive surfaces), so that adherends can be attached to the two sides of the adhesive tape, respectively, and can be suitable for joining adherends to each other. The adhesive tape of the present invention can be peeled off by heating, preferably resistance heating, and therefore, it is particularly suitable for use as a resistance heating (electric heating) peeling tape. The adhesive tape of the present invention can be suitably used for bonding adherends and separation of adherends as rigid bodies. The adhesive tape of the present invention can be easily peeled off by heating, and can therefore be used in applications where the adhesive tape needs to be peeled off when separating components for the purpose of reuse or recycling. For example, it can be suitably used as an adhesive tape for fixing components of various products in industrial applications such as electronic equipment, automobiles, building materials, OA, and home appliance industries, and the operating efficiency when separating components, peeling labels, etc. is improved.

[0089] [Method for producing adhesive tape] There is no particular limitation on the method for manufacturing the adhesive tape of the present invention. For example, the adhesive tape of the first embodiment of the present invention can be manufactured by applying a composition comprising components constituting an adhesive layer and a solvent on a release sheet and drying the composition to form an adhesive layer, applying a composition comprising components constituting a melt-softening layer and a solvent on another release sheet and drying the composition to form a melt-softening layer, and sequentially laminating them to the respective surfaces of a planar heating element. Here, the release sheet on the surface side of the melt-softening layer of the obtained adhesive tape is peeled off, and the adhesive layer formed on the release sheet is further laminated on the surface of the exposed melt-softening layer, thereby manufacturing the adhesive tape of the second embodiment of the present invention. Alternatively, after laminating the adhesive layer formed into a release sheet to one side of a planar heating element, a composition containing components constituting a melt-softening layer and a solvent is applied to the other side of the planar heating element and dried to form a melt-softening layer, thereby manufacturing the adhesive tape of the present invention in the first embodiment described above. In addition, by further laminating the adhesive layer formed on the release sheet to the surface of the melt-softening layer of the obtained adhesive tape, the adhesive tape of the present invention in the second embodiment described above can be manufactured. Furthermore, the composition containing the components constituting the adhesive layer and the composition containing the components constituting the melt-softened layer may be molded by extrusion molding, press molding, injection molding, or the like. The solvent is not particularly limited, and examples thereof include organic solvents such as toluene, xylene, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, and hexane; water, or an aqueous solvent mainly composed of water, etc. It should be noted that the solvent may remain in the adhesive layer and the melt-softened layer of the obtained adhesive tape, but it is generally preferred that the solvent is not contained.

[0090] 2. Items The present invention also provides an article comprising at least two adherends and the adhesive tape of the present invention between the two adherends, wherein the two adherends are bonded to each other via the adhesive tape. The adherend may be rigid or flexible like a film, etc. The material and shape of the adherend are not particularly limited, and examples thereof include plate-shaped adherends made of resin, glass or metal, housings and covers, and components having any of these on the adherend surface. The two adherends bonded via the adhesive tape may be the same or different. As a method for bonding adherends, there is a method of bonding the two adherends by attaching the adherends to the respective adhesive surfaces of the adhesive tape of the present invention. The article is not particularly limited, but is preferably, from the viewpoint of being able to effectively utilize the effects exerted by the pressure-sensitive adhesive tape of the present invention, electronic devices, components built into electronic devices, and the like. In the article of the present invention, the heat generating element constituting the pressure-sensitive adhesive tape preferably has a pair of extending portions extending from the outer periphery of an adherend in a plan view.

[0091] For example, Figure 6 Schematic top view and Figure 7 As shown in the schematic cross-sectional view in FIG, the article 100 of the present invention is an article comprising two adherends 50 and an adhesive tape 10 located between the two adherends 50, and the two adherends 50 are bonded via the adhesive tape 10, wherein the adhesive tape 10 comprises a laminated body laminated in the order of adhesive layer a / planar heating element b / melt-softening layer c. Figure 6 ) in which both ends of the planar heating element b in the long axis direction extend from the periphery of the adhesive layer a and the melt-softened layer c. In the article disassembly method described later, the two ends of the extended adhesive tape 10 can be used as a pair of terminals for electrical connection to a power source when the heating means is either resistance heating or heat conduction, or as ends in contact with a heat generating source, so that the heating element b of the adhesive tape 10 can be easily heated. Figure 6 As shown, in the plan view, the smaller the contact area between the adherend and the adhesive tape, the higher the heat generation efficiency of the heating element, and the easier it is to create an opportunity for disassembly during heating, which is advantageous in terms of easy disassembly. Although not shown in the figure, the article of the present invention may also include two adherends and a Figure 5 The adhesive tape shown is an article in which two adherends are bonded together via the adhesive tape.

[0092] In the top view of the article, the adhesive tape may be applied to the entire surface of the adhesive tape side of the adherend, that is, the adherend surface, or may be applied to a portion of the adherend surface. Figure 6As shown, it is preferred that the adhesive tape 10 is attached to a portion of the adherend surface of the adherend 50. In this case, the top view shape of the adhesive tape 10 in the article can be a strip or line shape, or a pattern shape. If the contact area between the adherend and the adhesive tape is small, when the adhesive tape is peeled off from the adherend by resistance heating, it is possible to easily generate a starting point for peeling between the adherend and the adhesive tape, which is advantageous from the perspective of easy peeling. In addition, in the top view of the article of the present invention, when the adhesive tape is adhered to the surface of the adhesive tape side of the adherend, that is, the entire area of ​​the adhered surface, the top view shape of the planar heating element in the adhesive tape can be the same shape as the top view shape of the adhesive tape, or it can be a strip, line or pattern.

[0093] 3. How to disassemble items The present invention also provides a method for disassembling the article of the present invention, wherein the two adherends are separated by melting or softening the melt-softening layer by heating with a heating element. The disassembly method of the present invention preferably includes a step of melting or softening the melt-softening layer by heating with a heat generating element to separate at least two adherends (separation step), and may include other steps as necessary. The heating means and method of the heating element are not particularly limited, and examples thereof include resistance heating, electromagnetic induction heating, infrared heating, microwave heating, heat conduction, etc. Among them, resistance heating is preferred.

[0094] When the heating of the heating element is resistance heating, the separation step is preferably the following step: the heating element is electrically connected to a power source, power is supplied to the heating element from the power source, and the molten-softening layer adjacent to the heating element is melted or softened by resistance heating, thereby separating the two adherends. The power source may be an external power source or a driving power source of an article that is an electronic device or a component built into the electronic device. In addition, when the article is an electronic device or a component built into the electronic device and the power source is a driving power source of the electronic device, the separation process is preferably a process of electrically connecting the heating element to the driving power source and circuit of the electronic device, energizing the heating element from the driving power source, and melting or softening the melt-softening layer by resistance heating, thereby separating the two adherends. The electrical connection method is to electrically connect a pair of extensions of the heating element extending from the periphery of the heating element or the adhesive layer and the molten softening layer to a power source using known means such as alligator clips. The circuit and the means of electrical connection are preferably formed of a conductive material that exhibits a volume resistivity different from that of the material of the heating element in the adhesive tape, and more preferably formed of a conductive material with a volume resistivity lower than that of the heating element. In this case, when the heating element is electrically connected to the circuit and power is supplied to the heating element from the driving power source, overheating of the circuit and the means of electrical connection can be prevented, and at the same time, voltage can be efficiently applied to the heating element so that it can be peeled off in a short time, which is advantageous.

[0095] The method of applying electricity can be appropriately selected according to the size of the adhesive tape or the type of the heating element of the present invention, and for example, a method of applying a voltage of 0.1 to 200 V until the melt-softening layer melts or softens (for example, in the range of 0.5 seconds to 30 minutes) can be cited. Figure 8 As shown schematically, a simple power source can be used. By electrically connecting the heating element of the adhesive tape of the present invention to a power source and applying a voltage to the heating element to energize it, the heating element and its periphery can be heated by resistance heating. By this heating, the melt-softening layer melts or softens, the bonding state is released, and it becomes possible to peel off, and the adherend becomes detachable.

[0096] The voltage applied to the heating element by energizing is usually preferably in the range of 0.1V to 200V, more preferably 0.5V to 150V, and further preferably 1.0V to 100V. Even if the voltage applied to the adhesive tape of the present invention is relatively low, the melting or softening of the melt-softening layer will occur in a short time. Therefore, by setting the voltage applied in the separation process to the above range, the article can be disassembled in a short time without applying excessive voltage, and the article can be prevented from being damaged by heat. In particular, by applying a voltage that can be coped with by articles such as small electronic devices and household electrical appliances, these articles can be easily disassembled.

[0097] The current applied to the heating element is not particularly limited, and is generally preferably in the range of 0.01A to 20A, more preferably 0.03A to 15A, further preferably 0.05A to 10A, and particularly preferably 0.1A to 5A. Since the melting or softening of the melt-softening layer of the adhesive tape of the present invention occurs in a short time, if the current applied in the separation process is set to the above range, the current flowing in general electronic devices and household appliances can be passed through, and the items can be disassembled in a short time, which can prevent the items from being damaged by heat. In particular, by applying a current that can be handled by small electronic devices and household electrical appliances, these items can be easily disassembled. The application time is not particularly limited, but is usually preferably 0.5 seconds to 30 minutes, more preferably 0.5 seconds to 120 seconds, and even more preferably 0.5 seconds to 30 seconds. If the application time is within the above range, the article will not be damaged by heat and can be easily disassembled in a short time.

[0098] When the heating of the heating element is electromagnetic induction heating, the separation step is preferably a step of separating the two adherends by melting or softening the melt-softening layer by electromagnetic induction heating using electromagnetic induction heating means. The electromagnetic induction heating means is not particularly limited, and a known electromagnetic induction heating device can be appropriately selected.

[0099] When the heating of the heating element is either infrared heating or microwave heating, the separation step is preferably a step of separating the two adherends by melting or softening the melt-softening layer by either infrared heating using infrared heating means or microwave heating using microwave heating means. There is no particular limitation on the infrared heating means and the microwave heating means, and a known infrared heating device and microwave heating device can be appropriately selected.

[0100] In the case where the heating of the heating element is conducted by heat conduction, the separation step is preferably a step of bringing the heating element into contact with the heat generating source and melting or softening the melt-softening layer by heat conduction, thereby separating the two adherends. The heat generating source is not particularly limited, and a known heater can be appropriately selected. The method of heat conduction using the heat generating source can be appropriately selected according to the size of the adhesive tape, the type of the heating element, etc., and for example, a method of bringing them into contact at a desired temperature until the melt-softening layer melts or softens can be cited.

[0101] The disassembly temperature of the article is preferably in the range of 80°C to 160°C, more preferably in the range of 90°C to 150°C, and further preferably in the range of 100°C to 130°C. By making the disassembly temperature within the above range, thermal damage to the article and the adherend can be suppressed, and the article can be easily disassembled. In particular, when the heating of the adhesive tape is resistance heating (electric heating), heat is directly generated inside the adhesive tape, and disassembly can be performed before the heat is transferred to the article and the adherend. The disassembly temperature of the article can be measured by using a temperature sensor using a thermocouple as the temperature of the heat generating element included in the pressure-sensitive adhesive tape of the present invention (the temperature reached by the heat generating element when disassembling the article).

[0102] The above is an explanation of one embodiment of the adhesive tape, article, and article disassembly method of the present invention, but the present invention is not limited to the configuration of the above embodiment. For example, the adhesive tape of the present invention may be supplemented with any other configuration in the configuration of the above embodiment, or may be replaced with any configuration that produces the same effect. Example

[0103] The present invention will be specifically described below by way of examples. However, the present invention is not limited to the following examples. The materials used in the examples and the like are shown below.

[0104] <Inorganic hollow fillers> Hollow filler 1: "Glass Bubbles S38" (trade name, manufactured by 3M Company, average particle size (median particle size) 40 μm, true density 0.38 g / cm 3 ) Hollow filler 2: "Glass Bubbles K15" (trade name, manufactured by 3M, average particle size (median particle size) 60 μm, true density 0.15 g / cm 3 ) <Heat generating element> Nickel-chromium alloy foil: "Nickel-chromium NCH1-H" [trade name, manufactured by Takeuchi Metal Foil Powder Industry Co., Ltd., thickness 10 μm. Volume resistivity 108 μΩ·cm (catalog value), 105 μΩ·cm (measured value)] <Peeling layer> Release liner: 75 μm thick polyethylene terephthalate film with release treatment on one side

[0105] <Constituent materials of the melt-softening layer (melt-softening resin composition) other than the inorganic hollow filler> [Preparation Example 1] 100 parts by mass of a styrene-isoprene block copolymer composition (a mixture of a styrene-isoprene diblock copolymer and a styrene-isoprene triblock copolymer; 24% by mass of structural units derived from styrene, 67% by mass of the styrene-isoprene diblock copolymer relative to the total amount of the composition), 40 parts by mass of Quintone G115 (C5 / C9 petroleum resin manufactured by Zeon Co., Ltd., Japan, softening point 115°C), and Pensel 30 parts by mass of D-160 (polymerized rosin ester resin manufactured by Arakawa Chemical Industries, Ltd., softening point 15°C to 150°C), 5 parts by mass of Nippon Polybutene HV-50 (polybutene manufactured by JX Nippon Mining and Energy Corporation, pour point -12.5°C), and 1 part by mass of an antioxidant (pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate) were mixed and dissolved in 100 parts by mass of toluene as a solvent to obtain a resin composition (P-1). The obtained resin composition (P-1) was applied to the release-treated surface of the release liner in a manner to have a thickness of about 2 mm after drying to produce a layer (P-1); a viscoelasticity tester (ARES-G2, manufactured by TA Instrument Japan Co., Ltd.) was used to measure the storage modulus G' and loss modulus (G") under the conditions of a frequency of 1 Hz, a temperature range of -40°C to 200°C, and a heating rate of 2°C / min. In addition, the tanδ of the above-mentioned resin composition (P-1) at a frequency of 1 Hz was calculated by the calculation formula [tanδ=G" / G']. The melting point of the resin composition (P-1) is 140°C, and the storage modulus G at 23°C is 23 2.5×10 5 Pa, storage modulus G at 120°C 120 5.0×10 4 Pa, the temperature at which tan δ reaches 0.8 is 125°C (the temperature range in which tan δ reaches 0.8 or higher is 125°C or higher).

[0106] <Materials for adhesive layer> [Preparation Example 2] Into a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, and a thermometer, 79.9 parts by mass of n-butyl acrylate, 6 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of cyclohexyl acrylate, 4 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 200 parts by mass of ethyl acetate were added, and nitrogen bubbling was performed at 23° C. for 1 hour under stirring to obtain a mixture. Next, 2 parts by mass of a 2,2′-azobis(2-methylbutyronitrile) solution (solid content: 1.0% by mass) previously dissolved in ethyl acetate was added to the mixture, and the mixture was stirred at 72° C. for 4 hours under stirring, and then stirred at 75° C. for 5 hours. Next, the obtained mixture was diluted with ethyl acetate and filtered with a 200-mesh metal mesh to obtain an acrylic copolymer (A-1) solution (solid content concentration: 26%) having a weight average molecular weight of 1,060,000 and an average carbon number of 4.4 in the saturated hydrocarbon group of the acrylic acid alkyl ester monomer. To 100 parts by mass of the obtained acrylic copolymer (A-1) solution was added 1.0 part by mass of an adduct of toluene diisocyanate and trimethylolpropane ("BURNOCK D-40" manufactured by DIC Corporation, an isocyanate crosslinking agent, solid content 40%, hereinafter referred to as "D-40") as a crosslinking agent to obtain a composition (P-2). The obtained composition (P-2) was applied to the release-treated surface of the release liner in a manner to have a thickness of about 2 mm after drying to produce a layer (P-2); a viscoelasticity tester (ARES-G2, manufactured by TA Instrument Japan Co., Ltd.) was used to measure the storage modulus G' and loss modulus (G") under the conditions of a frequency of 1 Hz, a temperature range of -40°C to 200°C, and a heating rate of 2°C / min. In addition, the tanδ of the above-mentioned composition (P-2) at a frequency of 1 Hz was calculated by the calculation formula [tanδ=G" / G']. The melting point of the composition (P-2) is 150°C or higher, and the storage modulus G at 23°C is 23 7.5×10 4 Pa, storage modulus G at 120°C 120 5.5×10 4 Pa, the temperature at which tan δ reaches 0.8 is higher than 150°C (the temperature range in which tan δ reaches 0.8 or higher is higher than 150°C). In addition, the maximum value of tan δ in the temperature range of 100°C to 150°C is 0.4.

[0107] 1. Examples of producing adhesive tape and articles [Example 1] <Manufacturing of adhesive tape> 30% by volume of hollow filler 1 was mixed into resin composition (P-1) to obtain adhesive (Y-1). Adhesive (Y-1) was applied to the release-treated surface of release liner in such a manner that the thickness after drying was 100 μm, and dried at 90° C. for 5 minutes to obtain melt-softened layer c1 (thermal conductivity 0.18 W / m·K). On the other hand, composition (P-2) was applied to the release-treated surface of the other release liner to a thickness of 50 μm after drying, and dried at 90° C. for 3 minutes to prepare an adhesive layer (thermal conductivity: 0.20 W / m·K). A molten softened layer c1 cut to a length of 50 mm and an arbitrary width was bonded to a nickel-chromium alloy foil of 100 mm in length by a hand roller, and the nickel-chromium alloy foil was positioned in such a way that both ends thereof in the length direction thereof protruded 25 mm. Similarly, an adhesive layer cut to a length of 50 mm and an arbitrary width was bonded to the opposite side of the nickel-chromium alloy foil bonded to the molten softened layer c1, and laminated from the upper surface of the release liner by a roller with a linear pressure of 5 kg / cm, and aged for 48 hours in an environment of 40°C. Thus, a laminated body in which the layers other than the release liner were laminated in the order of adhesive layer a1 / nickel-chromium alloy foil b / molten softened layer c1 was prepared, and the laminated body was in a shape in which both ends of the nickel-chromium alloy foil protruded 25 mm from the periphery of the molten softened layer c1 and the adhesive layer in the length direction of the nickel-chromium alloy foil, and the total thickness other than the release liner was 160 μm. The obtained laminate was cut into 2 mm width to obtain an adhesive tape (T-1), wherein the melt-softened layer c1 and the adhesive layer a1 were 2 mm wide × 50 mm long, and the nickel-chromium alloy foil b was 2 mm × 100 mm long, and the nickel-chromium alloy foil b had a pair of extensions extending from the periphery of the melt-softened layer c1 and the adhesive layer a1. A schematic top view of the adhesive tape (T-1) is shown in Fig. 9 , the schematic cross-section diagram is shown in Fig.10 .

[0108] <Production of items> For the adhesive tape of Example 1 ( Figures 11 to 13 The release liner on the side of the melt-softened layer c1 is peeled off and the release liner is attached to the adherend 50a (glass, 40 mm wide × 50 mm long × 10 mm thick) in a manner that the length of the tape adhesive surface (effective portion) is 50 mm and crosses the center of the adherend 50a in the width direction (refer to Figures 11 to 13 ). Next, the release liner on the adhesive layer a1 side was peeled off to form a shape in which the adhesive tape 10 was sandwiched between the adherend 50b (glass, 30 mm wide × 100 mm long × 2.8 mm thick) (refer to Figures 11 to 13 ) pasted at 20N / cm 2 The adhesive was pressed for 10 seconds, and the obtained adhered product was left to stand in an atmosphere of 23° C. and 50% RH for 24 hours or more, thereby obtaining the article of Example 1.

[0109] [Example 2] 60% by volume of the hollow filler 1 was mixed into the resin composition (P-1) to obtain an adhesive (Y-2). The adhesive (Y-2) was applied to the release-treated surface of the release liner in such a manner that the thickness after drying was 100 μm, and dried at 90° C. for 5 minutes to obtain a melt-softened layer c2 (thermal conductivity 0.16 W / m·K). Thereafter, the same procedure as in Example 1 was followed to produce an adhesive tape (T-2) and the article of Example 2.

[0110] [Example 3] 30% by volume of hollow filler 2 was mixed into the resin composition (P-1) to obtain an adhesive (Y-3). The adhesive (Y-3) was applied to the release-treated surface of the release liner in such a manner that the thickness after drying was 100 μm, and dried at 90° C. for 5 minutes to obtain a melt-softened layer c3 (thermal conductivity 0.16 W / m·K). Thereafter, the same procedure as in Example 1 was carried out to produce a pressure-sensitive adhesive tape (T-3) and the article of Example 3.

[0111] [Example 4] 60% by volume of the hollow filler 2 was mixed into the resin composition (P-1) to obtain an adhesive (Y-4). The adhesive (Y-4) was applied to the release-treated surface of the release liner in such a manner that the thickness after drying was 100 μm, and dried at 90° C. for 5 minutes to obtain a melt-softened layer c4 (thermal conductivity 0.13 W / m·K). Thereafter, the same procedure as in Example 1 was carried out to produce a pressure-sensitive adhesive tape (T-4) and the article of Example 4.

[0112] [Comparative Example 1] The resin composition (P-1) was applied to the release-treated surface of the release liner to a thickness of 100 μm after drying, and dried at 90° C. for 5 minutes to obtain a melt-softened layer c0 (thermal conductivity: 0.20 W / m·K). Thereafter, the same procedure as in Example 1 was carried out to produce a pressure-sensitive adhesive tape (CT-1) and an article of Comparative Example 1.

[0113] [Example 5] <Manufacturing of adhesive tape> In the same manner as in Example 1, a melt-softened layer c1 and an adhesive layer were prepared. The melt-softened layer c1 cut to a length of 50 mm and any width was attached to the nickel-chromium alloy foil of 100 mm in length by a hand roller, and the nickel-chromium alloy foil was positioned so that both ends in the length direction of the nickel-chromium alloy foil protruded 25 mm. Similarly, an adhesive layer cut to a length of 50 mm and any width was attached to the opposite side of the nickel-chromium alloy foil attached to the melt-softened layer c1, and laminated from the upper surface of the release liner by a roller with a linear pressure of 5 kg / cm. Next, an adhesive layer cut to a length of 50 mm and an arbitrary width was attached to the surface of the melt-softened layer c1 from which the release liner was peeled, and laminated from the upper surface of the release liner using a roller with a linear pressure of 5 kg / cm, and aged for 48 hours at 40°C. Thus, a laminated body was prepared in which the layers other than the release liner were laminated in the order of adhesive layer a1 / nickel-chromium alloy foil b / melt-softened layer c1 / adhesive layer a2, and the two ends of the nickel-chromium alloy foil were extended by 25 mm from the periphery of the melt-softened layer and the adhesive layer in the longitudinal direction of the nickel-chromium alloy foil, and the total thickness other than the release liner was 210 μm. The obtained laminate was cut into a width of 2 mm to obtain an adhesive tape (T-5), wherein the melt-softening layer and the adhesive layer had a size of 2 mm wide × 50 mm long, and the nickel-chromium alloy foil had a size of 2 mm × 100 mm long, and the nickel-chromium alloy foil had a pair of extensions extending from the periphery of the melt-softening layer and the adhesive layer.

[0114] <Production of items> For the adhesive tape of Example 5 ( Figures 11 to 1310), peel off one release liner on the adhesive layer a1 side, and stick it to the adherend 50a (glass, width 40mm×length 50mm×thickness 10mm) in a manner that the length of the tape adhesive surface (effective portion) is 50mm and crosses the center of the adherend 50a along the width direction of the adherend 50a (refer to Figures 11 to 13 ). Next, the other release liner on the adhesive layer a2 side was peeled off to form a shape in which the adhesive tape 10 was sandwiched between the adherend 50b (glass, 30 mm wide × 100 mm long × 2.8 mm thick) (refer to Figures 11 to 13 ) pasted at 20N / cm 2 The adhesive was pressed for 10 seconds, and the obtained adhered product was left to stand in an atmosphere of 23° C. and 50% RH for 24 hours or more, thereby obtaining an article of Example 5.

[0115] [Example 6] 60% by volume of the hollow filler 1 was mixed into the resin composition (P-1) to obtain an adhesive (Y-2). The adhesive (Y-2) was applied to the release-treated surface of the release liner in such a manner that the thickness after drying was 100 μm, and dried at 90° C. for 5 minutes to obtain a melt-softened layer c2 (thermal conductivity 0.18 W / m·K). An adhesive tape (T-6) and an article of Example 6 were prepared by the same procedure as in Example 5, except that the melt-softening layer c2 was used instead of the melt-softening layer c1.

[0116] [Example 7] 30% by volume of hollow filler 2 was mixed into the resin composition (P-1) to obtain an adhesive (Y-3). The adhesive (Y-3) was applied to the release-treated surface of the release liner in such a manner that the thickness after drying was 100 μm, and dried at 90° C. for 5 minutes to obtain a melt-softened layer c3 (thermal conductivity 0.16 W / m·K). An adhesive tape (T-7) and an article of Example 7 were prepared by the same procedure as in Example 5, except that the melt-softening layer c3 was used instead of the melt-softening layer c1.

[0117] In addition, the thermal conductivity of the melt-softened layer and the adhesive layer in the examples and comparative examples is a value measured by a rapid thermal conductivity meter ("QTM-710" manufactured by Kyoto Electronics Industry Co., Ltd.).

[0118] 2. Evaluation For the articles obtained in each example and comparative example, Figures 11 to 13 The pushing strength was measured using the apparatus shown in the figure as follows. (1) Push strength before heating The articles obtained in each example and comparative example were used as test pieces and were heated at 23°C. Fig.11 The pressing position of Figures 12-13 The probe 70 shown pressed the glass plate in the direction of the arrow at a speed of 10 mm / min to measure the strength when the adhesive tape was peeled off [pressing strength (G1)]. (2) Pushing strength after heating for 10 seconds The articles obtained in each example and comparative example were used as test pieces, and the extension e of the nickel-chromium alloy foil (heating element) in the adhesive tape 10 of each test piece was clamped with an alligator clip 60, and a DC stabilized power supply (manufactured by Kikusui Electronics Industry Co., Ltd., trade name "PAS160-1") was used to pass a current of 0.5 A or 1.0 A. After 10 seconds from the start of power-on, the power was continued while using Figures 12-13 The probe 70 shown pressed the glass plate in the direction of the arrow at a speed of 10 mm / min to measure the strength when the adhesive tape was peeled off [pressing strength (G2)]. It should be noted that the temperature of the heating element reached when the heating was disassembled at 0.5A (the disassembly temperature of the article) was about 100°C, and the temperature of the heating element reached when the heating was disassembled at 1.0A (the disassembly temperature of the article) was about 160°C. The temperature of the heating element after energization was measured by a temperature sensor using a thermocouple. (3) Residual adhesive force and push strength reduction rate The residual adhesive force and the reduction rate of the pushing strength were calculated using the following formula using the pushing strength (G1) and the pushing strength (G2), and the disassembly property was evaluated according to the following criteria. Residual adhesion (%) = 100 × G2 / G1 Pushing strength reduction rate (%) = 100 × [1-(G2 / G1)] [Evaluation criteria for disassembly] ◎: Residual adhesive force is less than 50% ○: Residual adhesive force is 50% or more and less than 65% △: Residual adhesive force is more than 65% The above results are summarized in Table 1.

[0119] [Table 1]

[0120] The pressing strength of the adhesive tapes of each embodiment after energization and heating is smaller than that of the comparative example. In particular, when the energized current is set to 1A, the residual adhesive force after energization relative to the initial adhesive force is small, and the reduction rate of the adhesive force (reduction rate of the pressing strength) caused by energization is greater than that of the comparative example. In addition, for the adhesive tapes of Examples 5 to 7 in which an adhesive layer is further provided on the opposite side of the surface of the melt-softening layer adjacent to the heating element, the initial push-out strength is higher than that of the adhesive tape of the comparative example, and the reduction rate of the adhesive force (the reduction rate of the push-out strength) caused by energization is greater than that of the adhesive tape of the comparative example. That is, due to the heat storage effect of the melt-softening layer, the adhesive force is weakened by the heating from the heating element, and the disassembly of the articles made using the adhesive tapes of each example is excellent. Industrial Applicability

[0121] The adhesive tape of the present invention can be peeled off by heating in a short time, can prevent thermal damage to the adherend, and the operation of heating and peeling is easy. Therefore, the adhesive tape of the present invention can be suitably used for applications where it is necessary to peel off the adhesive tape when separating components for the purpose of reuse or recycling, such as adhesive tapes used to fix components of various products in industrial applications such as electronic equipment, automobiles, building materials, OA, and home appliance industries, and can improve the operating efficiency when separating components, peeling labels, etc.

Claims

1. An adhesive tape, characterized in that: The device comprises at least an adhesive layer, a heating element, and a melt-softened layer adjacent to the heating element in this order, The melt-softened layer contains a thermoplastic resin and an inorganic hollow filler.

2. The adhesive tape according to claim 1, wherein The thermoplastic resin constituting the melt-softened layer includes a block copolymer or a hydrogenated product thereof, wherein the block copolymer includes a polymer block including a structural unit derived from an aromatic vinyl compound and a polymer block including a structural unit derived from a conjugated diene compound.

3. The adhesive tape according to claim 1, wherein The blending amount of the inorganic hollow filler in the melt-softened layer is in the range of 5 volume % to 80 volume %.

4. The adhesive tape according to claim 1, wherein The average particle size of the inorganic hollow filler is in the range of 1 μm to 200 μm.

5. The adhesive tape according to claim 1, wherein The inorganic hollow filler is at least one selected from glass hollow fillers and silica hollow fillers.

6. The adhesive tape according to claim 1, wherein The thickness of the melt-softened layer is in the range of 10 μm to 200 μm.

7. The adhesive tape according to claim 1, wherein The thermal conductivity of the melt-softened layer is in the range of 0.03 W / m·K to 0.20 W / m·K.

8. The adhesive tape according to claim 1, wherein The temperature range in which the loss tangent tanδ of the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softened layer reaches 0.8 or more is 80° C. or more.

9. The adhesive tape according to claim 1, wherein The temperature at which the loss tangent tanδ of the adhesive layer reaches 0.8 or more is higher than the temperature at which the loss tangent tanδ of the component containing the thermoplastic resin other than the inorganic hollow filler constituting the melt-softened layer reaches 0.8 or more.

10. The adhesive tape according to claim 1, wherein The heating element has a volume resistivity of 30 μΩ·cm or more at 20° C.

11. The adhesive tape according to claim 1, wherein The heat generating element has a pair of protruding portions protruding from the outer peripheries of the adhesive layer and the melt-softened layer in a plan view.

12. The adhesive tape according to claim 1, wherein The melt-softened layer further includes an adhesive layer on the side of the surface opposite to the surface adjacent to the heating element.

13. The adhesive tape according to claim 1, wherein The melt-softened layer can be peeled off by heating.

14. The adhesive tape according to claim 1, wherein The heating element is a current-carrying element that generates heat when electricity is passed through it, and the adhesive tape is peeled off by the heat generated by the current-carrying element.

15. An article, characterized in that Include: At least 2 adherends; and The adhesive tape according to any one of claims 1 to 14 between the two adherends, The two adherends are bonded together via the adhesive tape.

16. The article of claim 15, wherein: The heat generating element constituting the pressure-sensitive adhesive tape has a pair of extending portions extending from the outer periphery of the adherend in a plan view.

17. The method for disassembling an article according to claim 15, characterized in that: The heat of the heating element causes the melt-softening layer to melt and / or soften, thereby separating the two adherends.

18. The method for disassembling an article according to claim 17, wherein: The heating of the heating element is resistance heating. The heating element is electrically connected to a power source, and current is supplied from the power source to the heating element, so that the melt-softening layer is melted and / or softened by resistance heating, thereby separating the two adherends.

Citation Information

Patent Citations

  • Hot-melt type adhesive composition

    JP2002188068A

  • Demolition method for building

    JP2006200279A

  • Double-sided adhesive tape and method for producing the same, adhering and separating double-sided adhesive tape

    JP2016108394A